Impact of non-hip fractures in elderly women: a narrative review. (4th May 2022) - Charles, A.; Mugisha, A.; Iconaru, L.; Baleanu, F.; Benoit, F.; Surquin, M.; Bergmann, P.; Body, J. J.
Abstract: The association of hip fractures with adverse outcomes is well established, but for non-hip fractures this association still needs to be further investigated. The objective of this narrative review is to describe the state of the art with regards to the health impact of clinically relevant non-hip fracture locations in postmenopausal women. PubMed and Scopus databases were searched from January 2010 until December 2020. Studies were included when the crude rates and/or relative risk of 1-year subsequent fractures and/or mortality were reported as well as the precise fracture site. Twenty-three studies met the inclusion criteria. Regarding mortality rates, there was a high variability between studies, with higher rates for vertebral, proximal humerus and pelvic fractures. There was a small or no impact of wrist, ankle or tibia fractures. The mortality rate increased with age after vertebral, proximal humerus and wrist fractures. Moreover, proximal humerus and vertebral fractures were associated with a higher mortality risk. This narrative review indicates that, besides fractures of the hip, fractures of the vertebrae, proximal humerus or pelvis deserve more attention when trying to prevent adverse outcomes of osteoporosis. More studies on the topic of non-hip fractures are urgently needed.